Motor Vehicle Tax Collection Potential and Fees for Returning the Name of Motor Vehicles in Belu Regency, Nusa Tenggara Timur - Heru Sudinta; Dwikora Harjo; Iwan Irwansyah; Francky William Leonardo Lona (East Asian Journal of Multidisciplinary Research, 2022)
Regional Taxes in Indonesia consist of several types of tax objects, one of which is Motor Vehicle Tax (PKB) and Motor Vehicle Name Transfer Fee (BBNKB). There are still many obstacles that cause the realization of this type of tax revenue in certain years not to meet the targets set by the Government, including revenues in Belu Regency, East Nusa Tenggara. In 2017 PKB revenues reached 98.49% and BBNKB 98.03%, in 2018 PKB reached 101.10% and BBNKB 104.40%, in 2019 PKB only reached 76.56% and BBNKB 79.74%. On the other hand, the number of registered motorized vehicles has increased every year. This study was conducted to analyze the Potential for Collecting Motor Vehicle Taxes and Motor Vehicle Transfer Fees at the Atambua Samsat Joint Office, Belu Regency, East Nusa Tenggara Province from 2017 to 2019. Kenneth Davey's potential theory is used as a reference in this study, this theory says that to assessing the potential and performance of a type of levy requires the fulfillment of several dimensions, namely adequacy and elasticity, fairness, administrative capacity, political agreement, economic efficiency and suitability as a regional levy. The approach used in this research is a qualitative approach with a descriptive method. Collecting data in this study by conducting observations, documentation and interviews. The results of this study indicate that the Potential for Collecting PKB and BBNKB in 2019 did not reach the target due to several obstacles faced by the Atambua Samsat Joint Office, such as the lack of infrastructure, public awareness and knowledge about PKB and BBNKB which is still low.